The dynamics of customer value and brand love among shoppers in emerging market - Hayford Amegbe; Charles Hanu; Nkululeko PraiseGod Zungu (Cogent Business & Management, 2023)
This study examines customer value, trust, psychological ownership, satisfaction, and brand love among customers of shopping malls. This study employed a quantitative research design. An online questionnaire was used to elicited data from 484 Ghanaian shopping mall customers in Accra, using convenient sampling. Seven hypotheses were developed and tested using structural equation modelling (SEM). The study finds that utilitarian and social values predict trust, while trust influences psychological ownership. Additionally, psychological ownership influences satisfaction and brand love, while satisfaction affects brand love. The study's value rests in introducing relatively new constructs, such as psychological ownership and brand love to understand how customer value can be achieved, especially from a developing country's context, where there is a paucity of such studies.
Keywords: 650; and brand love; customer value; psychological ownership; satisfaction; trust